2022
DOI: 10.3390/su14052806
|View full text |Cite
|
Sign up to set email alerts
|

Exogenous Caffeine (1,3,7-Trimethylxanthine) Application Diminishes Cadmium Toxicity by Modulating Physio-Biochemical Attributes and Improving the Growth of Spinach (Spinacia oleracea L.)

Abstract: Leafy vegetables usually absorb and retain heavy metals more readily than most of the other crop plants, and thus contribute ≥70% of the total cadmium (Cd) intake of humans. Caffeine mediates plant growth and has proved to be beneficial against pathogens and insects. Therefore, it was hypothesized that foliar applications of caffeine could alter metabolism and reduce Cd toxicity in spinach (Spinacia oleracea L.). Seven-day old spinach seedlings were provided with Cd (0, 50, and 100 µM) stress. Caffeine (0, 5, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 70 publications
3
8
0
Order By: Relevance
“…The current study shows that these contents significantly decreased with increasing metal (Pb and Cd) concentrations in plant tissues as shown in Table 4. The chlorophyll and carotenoid contents in plants exhibited the same trend of under Pb and Cd exposure as demonstrated by Emanuil et al [74] and Rahman et al [75]. We observed a decrease in carotenoid contents when the Pb and Cd concentrations were higher.…”
Section: Carotenoid and Chlorophyll Contents In Plantssupporting
confidence: 88%
See 2 more Smart Citations
“…The current study shows that these contents significantly decreased with increasing metal (Pb and Cd) concentrations in plant tissues as shown in Table 4. The chlorophyll and carotenoid contents in plants exhibited the same trend of under Pb and Cd exposure as demonstrated by Emanuil et al [74] and Rahman et al [75]. We observed a decrease in carotenoid contents when the Pb and Cd concentrations were higher.…”
Section: Carotenoid and Chlorophyll Contents In Plantssupporting
confidence: 88%
“…Vijayarengan [43] found that increased zinc level in the soil results in decreasing the chlorophyll and carotenoid contents in the leaves of radish plant. A similar change in chlorophyll contents was recorded with Pb and Cd treatments [74,75]. The carotenoid contents decreased with increasing Pb, Cd concentrations demonstrated in various treatments.…”
Section: Carotenoid and Chlorophyll Contents In Plantssupporting
confidence: 79%
See 1 more Smart Citation
“…Human exposure to HMs has intensely increased due to exponential growth in various industries [6][7][8][9][10]. The solid waste or liquid effluent contaminates water and surface soil, entering the food chain through plants or aquatic organisms and resulting in adverse effects on human health [11].…”
Section: Introductionmentioning
confidence: 99%
“…During the degradation of caffeine, several metabolites are generated, which could act as modulators of the plant stress response, potentially increasing antioxidant contents and conferring tolerance (Ashihara et al, 2008; Watanabe et al, 2014). Emanuil et al (2022) observed improved plant tolerance and increased antioxidant content in spinach after caffeine application, suggesting the potential use of this alkaloid as a component of biostimulants, which could potentially enhance plant productivity and/or quality.…”
Section: Introductionmentioning
confidence: 99%